Overexpression of tissue factor induced atherothrombosis in apolipoprotein E−/− mice via both enhanced plaque thrombogenicity and plaque instability. (February 2019) - Liu, Xiaoling; Ma, Jing; Ma, Lianyue; Liu, Fangfang; Zhang, Cheng; Zhang, Yun; Ni, Mei
Abstract: The mechanisms leading to atherothrombosis from "vulnerable plaque" are more complex than initially proposed. We aimed to clarify whether plaque thrombogenicity is critical in atherothrombosis in mice. In a murine model of plaque destabilization, we enhanced plaque thrombogenicity by systemically overexpressing murine tissue factor (TF) by adenovirus-mediated gene transfer. The potential effects and mechanisms of TF on plaque destabilization were examined in cultured human aortic smooth muscle cells (HASMCs), RAW264.7 cells and human umbilical vein endothelial cells (HUVECs). To elucidate the TF noncoagulant effects on plaque destabilization, TF-overexpressed mice were treated with the protease-activated receptor 2 (PAR-2) antagonist ENMD-1068. In TF-overexpressing apolipoprotein (E)–deficient (ApoE−/−) mice, 67% (8 of 12) of carotid plaques exhibited plaque disruption and atherothrombosis. Moreover, 58% (7 of 12) showed plaque hemorrhage, including 1 due to plaque disruption, 4 neovascularization and 2 both. In contrast, only 17% (2 of 12) of control mice showed atherothrombosis, both with plaque hemorrhage but no neovascularization. On PCR, TF overexpression increased the expression of inflammatory factors. In cultured cells, the TF–FVIIa complex enhanced the expression of inflammatory factors and a vicious cycle of inflammation. Also, TF–FVIIa complex induced intra-plaque angiogenesis via PAR-2. ENMD-1068 treatment significantly inhibited the expression of inflammatory factors and neovascularization, and the incidence of intra-plaque hemorrhage decreased in TF-overexpressing mice. In conclusions, TF overexpression enhanced plaque thrombogenicity, which played a pivotal role in atherothrombosis in ApoE−/− mice. In addition, TF promoted plaque instability by activating inflammatory and proangiogenic effects via TF–FVIIa/PAR-2 signaling.